Peran Lingkungan Keluarga Dan Efikasi Diri Yang Memotivasi Mahasiswa Untuk Menjadi Young Entreprenuer - Munawir Nasir; Muhammad Haerdiansyah Syahnur (AkMen JURNAL ILMIAH, 2021)
The open unemployment rate (TPT) for university graduates with a bachelor's degree is becoming increasingly concerning, owing largely to an increase in the workforce that has not been fully absorbed by employment. The first observations were made on 50 students who were interviewed about their interest and motivation to become young entrepreneurs. It was discovered that only 28% of students were interested in becoming entrepreneurs, while 72% were not. The purpose of this study was to determine what factors, in terms of family environment and self-efficacy, can motivate students to become young entrepreneurs. This study employs a quantitative method of causal experimental design to determine the influence and relationship between two variables. The research questions were developed using three operational variables: family environment, self-efficacy, and motivation to pursue a career as a young entrepreneur. The research questions were distributed online to students still enrolled at the strata-1 level, and a total of 329 respondents were obtained. The PLS-SEM application is used to conduct testing and analysis. The study's findings indicate that Family Environment and Self-Efficacy both have a positive, significant effect on motivation to become a young entrepreneur. In the original sample, the T statistic for self-efficacy was greater than the T statistic for the family environment. Thus, this demonstrates that the self-efficacy variable plays a larger role in motivating students to become young entrepreneurs than the family environment does. Additionally, the indicators examined in this study can be used to motivate education providers, particularly universities, to take a more proactive role in motivating students to be motivated by a strong desire to pursue employment opportunities upon graduation.